Detection of Microsatellite Instability in Colorectal Cancer Patients With a Plasma-Based Real-Time PCR Analysis - Kim, Namjoo; Kim, Sung Min; Lee, Beom Jae; Choi, Byung il; Yoon, Hee Sook; Kang, Sang Hee; Kim, Seung Han; Joo, Moon Kyung; Park, Jong-Jae; Kim, Chungyeul (Frontiers in Pharmacology, 2021)
A microsatellite instability (MSI) test is crucial for screening for HNPCC (Hereditary nonpolyposis colorectal cancer; Lynch syndrome) and optimization of colorectal cancer (CRC) treatment. Mismatch repair (MMR) deficiency is a predictor for good response of immune checkpoint inhibitors in various malignancies. In this study, we evaluated the results of a newly developed plasma-based real-time PCR kit for the detection of MSI in CRC patients. We assessed a peptide nucleotide acid (PNA) probe-mediated real-time PCR test (U-TOP MSI Detection Kit Plus) that determines MSI status by using amplicon melting analysis of five markers (NR21, NR24, NR27, BAT25, and BAT26) from plasma. Eighty-four CRC patients (46 dMMR and 38 pMMR) with colorectal cancer were analyzed. The concordance rate of MSI status assessment between the plasma kit and IHC was 63.0% in dMMR patients (29/46), but in the pMMR evaluation, a 100% (38/38) concordance rate was observed. In the evaluation of the performance of a custom tissue U-TOP MSI Detection Kit and plasma kit in 28 patients, sensitivity, specificity, PPV (positive predictive value) and NPV (negative predictive value) of plasma kit were 68.4, 100, 100, and 44.4%, respectively, with the tissue U-TOP MSI Detection Kit. Our results demonstrate the feasibility of a non-invasive and rapid plasma-based real-time PCR kit (U-TOP MSI Detection Kit Plus) for the detection of MSI in colorectal cancer.